Severe nephropathy in three adolescents with cystic fibrosis. Issue 12 (December 1991) - Melzi, M L; Costantini, D; Giani, M; Appiani, A C; Giunta, A M
Abstract : Renal involvement has rarely been reported in patients with cystic fibrosis. We describe severe nephropathy with a rapidly fatal outcome in three adolescents with cystic fibrosis, and evaluate the important repercussions that the nephrotic syndrome had on the precarious clinical situation of these patients.